Negosiasi Identitas Budaya Perantau Minangkabau Di Kota Bandung: Implementasi Filosofi “Di Mana Bumi Dipijak, Di Situ Langit Dijunjung” (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The objective of this research is to examine how Minangkabau migrants in Bandung negotiate their cultural identity and how the philosophy "di mana bumi dipijak, di situ langit dijunjung" is implemented in their social adaptation. Data were collected through in-depth interviews with migrant students from West Sumatra at Universitas Pendidikan Indonesia, utilizing a qualitative approach and phenomenological method. The study indicates that Minangkabau migrants actively and dynamically negotiate their identity through integration patterns rather than assimilation. Situational strategies are employed; informants gain social acceptance by adopting local linguistic identities and behaviors (Sundanese) in public spaces, while maintaining core values in private spaces. The religious principles of Adat Basandi Syarak, Syarak Basandi Kitabullah, and the communication ethics of Kato Nan Ampek serve as adaptation guidelines that allow for external flexibility, such as in language and daily habits, while preserving fundamental, non-negotiable values. The success of this negotiation is significantly supported by the educational environment and the early internalization of traditional values. This process results in a hybrid identity, enabling migrants to preserve their authentic Minangkabau identity while becoming an integral part of the Bandung community.